Invesigate how cultural and socioeconomic factors influence oral cancer prevention behaviors, screening uptake, and treatment outcomes - Madhu Ranjan; Tushar; Nirav Hemant Parekh; Arti Dixit; Pinaki Rakshit; Bhagyashree P Agre; Bhumika Kamal Badiyani; Amit Kumar (Wolters Kluwer Medknow Publications, 2024)
Background: Oral cancer is a significant global health issue, with prevention and early detection being pivotal for improved outcomes. This study investigates the impact of cultural and socioeconomic factors on oral cancer prevention behaviors, screening participation, and treatment outcomes. Materials and Methods: A cross-sectional study design was employed, involving a sample size of 1,000 participants. Participants were recruited through stratified sampling to ensure cultural and socioeconomic diversity. Statistical analyses, including logistic regression, were used to explore associations between factors and outcomes. Results: The study revealed multifaceted influences of cultural and socioeconomic factors on oral cancer-related aspects. Cultural factors significantly influenced prevention behaviors, with participants from certain cultural backgrounds exhibiting higher rates of tobacco use and lower rates of dietary adherence). Socioeconomic status played a role in screening uptake, with individuals from lower income brackets less likely to undergo regular screenings. Conclusion: Cultural and socioeconomic factors have a substantial influence on oral cancer prevention behaviors, screening participation, and treatment outcomes.